Enhanced root traits and productivity of maize (Zea mays) and wheat (Triticum aestivum) in maize - wheat cropping system through integrated potassium management - KUMAR, SANJEEV; DHAR, SHIVA; OM, HARI; MEENA, RANG LAL (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during the kharif and rabi seasons of 2010-11 and 2011-12 at Indian Agricultural Research Institute, New Delhi to find out the performance of maize (Zea mays L.) - wheat (Triticum aestvum L.) cropping system with potassium (K) fertilization through muriate of potash and farmyard manure. Ten treatments were evaluated in randomized block design with three replications. All the treatment with potassium irrespective of sources showed significant increase in grain yield. Application of 60 kg K through muriate of potash + 30 kg K through farmyard manure produced highest grain yield of maize (4.44 and 5.42 tonnes/ha) and wheat (5.39 and 5.49 tonnes/ha), which was significantly superior over grain yield of maize (2.21 and 2.72 tonnes/ha) and wheat (3.80 and 3.89 tonnes/ha) as obtained from control during both the years. Application of K showed better root growth over no K application. In maize, application of 90 kg K/ha, supplemented 60 kg K/ha through MOP and 30 kg K/ha through farmyard manure (FYM) recorded highest root length density (4.51 and 4.33 cm/cm3), surface area density (1.31 and 1.11 cm2/ cm3) root volume density (30.5 and 28.6 cm3/cm3) and dry weight (9.0 and 10.1 g/plant). Similarly, in wheat the same treatment also recorded highest root length density (2.7 and 3.03 cm/cm3), surface area density (0.60 and 0.64 cm2/ cm3), root volume density (12.52 and 16.9 cm3/cm3) and dry weight (2.43 and 2.84 g /plant) during both the years.